(untitled) (Studia theodisca, 2023)
The following paper discusses Schiller’s interpretation of the German concept of Bildung, which appears to be a central term in Germany’s culture, especially (but not limited to) the educational realm. As Bildung underwent massive transformations and has been re-interpreted multiple times throughout German history, this paper will start with a definitory exercise trying to organize the dynamics surrounding the term. Secondly, a two-fold historical context – firstly regarding the wider political and social dynamics of the time and secondly, a more biographical approach focusing on Schiller – will be provided. These contextualizing efforts will be succeeded by elaborations on Schiller’s concept of Herzensbildung. The paper closes with a summary of key insights and further potential endeavors.